Small Cities and Towns in Global Era (Edited by R.N. Sharma and R.S.Sandhu (2013), Rawat Publications, Jaipur - Singh, Arun K. (National Geographical Journal of India, 2022)
The new market system emerged under the new global regime, have made significant impact on the conventionally existing cities and there is a strong need of understanding the impact of such changes on Indian urban settlements, particularly small cities and towns which have been on the margins. This volume has come out of the papers presented in a national seminar organized at the Tata Institute of Social Sciences (TISS), Mumbai in August 2011.The book is divided into two sections containing sixteen papers. The first section gives the theoretical perspectives of small cities and towns in the globalised world and the second section deals with case studies.